Entrepreneurial Orientation and Organizational Resilience: Role of Leadership Ambidexterity - Neswardi, Sepri; Rasyid, Rosyeni; Abror, Abror (Universitas Negeri Padang, 2025)
This study examines the impact of Entrepreneurial Orientation (EO) on Organizational Resilience (OR) while considering the mediating role of Leadership Ambidexterity (LA) in the context of Small and Medium Enterprises (SMEs) in West Sumatra. A quantitative causal research approach was employed, utilizing Structural Equation Modeling (SEM) to analyze data collected from 172 SMEs. Confirmatory Factor Analysis was conducted to ensure the validity and reliability of the measurement model. The findings indicate that EO positively and significantly influences OR (β = 0.431, p < 0.001) and has a significant effect on LA (β = 0.291, p < 0.001), which in turn impacts OR (β = 0.485, p < 0.001). The mediation analysis confirms that LA partially mediates the EO-OR relationship (β = 0.287, p < 0.001), suggesting that while EO directly strengthens OR, leadership ambidexterity enhances this relationship further. These results highlight the importance of fostering entrepreneurial proactiveness, risk-taking, and innovation, along with adaptive leadership strategies to enhance SMEs’ resilience. This study contributes to the literature by emphasizing the strategic role of ambidextrous leadership in driving organizational adaptability and sustainability. Practical implications suggest that SME leaders should integrate exploratory and exploitative leadership approaches to strengthen resilience and improve business performance.